Internet addictive behavior in adolescence: A cross-sectional study in seven European countries - Tsitsika, A.; Janikian, M.; Schoenmakers, T.M.; Tzavela, E.C.; Ólafsson, K.; Wójcik, S.; Macarie, G.F.; Tzavara, C.; Richardson, C. (2014)
A cross-sectional school-based survey study (N=13,284; 53% females; mean age 15.8±0.7) of 14-17-year-old adolescents was conducted in seven European countries (Greece, Spain, Poland, Germany, Romania, the Netherlands, and Iceland). The aim of the study was to investigate the prevalence of Internet addictive behavior (IAB) and related psychosocial characteristics among adolescents in the participating countries. In the study, we distinguish two problematic groups: adolescents with IAB, characterized by a loss of control over their Internet use, and adolescents "at risk for IAB," showing fewer or weaker symptoms of IAB. The two groups combined form a group of adolescents with dysfunctional Internet behavior (DIB). About 1% of adolescents exhibited IAB and an additional 12.7% were at risk for IAB; thus, in total, 13.9% displayed DIB. The prevalence of DIB was significantly higher among boys than among girls (15.2% vs. 12.7%, p<0.001) and varied widely between countries, from 7.9% in Iceland to 22.8% in Spain. Frequent use of specific online activities (e.g., gambling, social networking, gaming) at least 6 days/week was associated with greater probability of displaying DIB. Multiple logistic regression analysis indicated that DIB was more frequent among adolescents with a lower educational level of the parents, earlier age at first use of the Internet, and greater use of social networking sites and gaming sites. Multiple linear regression analysis showed that externalizing (i.e., behavioral) and internalizing (i.e., emotional) problems were associated with the presence of DIB. © Copyright 2014, Mary Ann Liebert, Inc. 2014.